1987
DOI: 10.1073/pnas.84.12.4135
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal activation of ionic currents in follicle-enclosed Xenopus oocytes.

Abstract: Membrane currents were recorded, using the voltage clamp technique, from Xenopus laevis oocytes still surrounded by their enveloping follicular and epithelial cells. Exposure of the follicles to mammalian gonadotropins elicited a current generated largely by an increase in membrane K' conductance. The gonadotropin response resembled responses elicited by adenosine and catecholamines in the same follicle, but was not blocked by purinergic or catecholaminergic antagonists. The gonadotropin-induced currents were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…The first (1 in Fig. 1 A ) was an outward current (FSH-K+), associated with an increase in K ÷ conductance caused by an intraceUular rise in cAMP (Woodward and Miledi, 1987a). This first component was frequently cut short by the development of a second component (2 in Fig.…”
Section: Components Of the Membrane Currents Elicited By Fsh And Ach mentioning
confidence: 99%
See 2 more Smart Citations
“…The first (1 in Fig. 1 A ) was an outward current (FSH-K+), associated with an increase in K ÷ conductance caused by an intraceUular rise in cAMP (Woodward and Miledi, 1987a). This first component was frequently cut short by the development of a second component (2 in Fig.…”
Section: Components Of the Membrane Currents Elicited By Fsh And Ach mentioning
confidence: 99%
“…Activation of these receptors stimulates the synthesis of adenosine 3':5'-cyclic monophosphate (cAMP) and activates a K + current via intermediate steps still not well characterized. Previous studies have strongly suggested that all the elements involved in this type of follicle response are in the follicular cell compartment and not in the oocyte (Woodward and Miledi, 1987a;Miledi and Woodward, 1989a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…follicles that showed residual responses to ␤,␥-meATP were also tested with ATP alone (1-100 M) or coapplied with a threshold concentration of forskolin (FSK), a drug that directly activates adenylyl cyclase; thereby, increasing the synthesis of cAMP. In the Xenopus follicle, FSK strongly potentiates I K,cAMP responses to specific stimulation of different receptors coupled to cAMP synthesis (1,20), including responses to Ado and ATP in w.f. (4,10,13).…”
Section: Relationship Of Current Responses Elicited By Purinergic Agomentioning
confidence: 99%
“…UTP is a specific agonist of F Cl , and shows a weak or null capacity to generate I K,cAMP (8). In this series of experiments, I K,cAMP was elicited by Ado (10 M) or by follicle-stimulating hormone (0.5 g/mL) (20), and the amplitude of I K,cAMP was compared with that obtained in the presence of UTP (100 M), using a 40-s preincubation with UTP alone to ensure maximal effect (Fig. 3A).…”
Section: Relationship Of Current Responses Elicited By Purinergic Agomentioning
confidence: 99%